Characterization of incidental cardiac masses in oncological patients using a new CT-based tumor volume perfusion technique. (October 2013) - Schulze, M; Spira, D; Claussen, CD; Sauter, A; Mayer, F; Horger, M
Cardiac masses are challenging for non-invasive diagnostic procedures and therapy, respectively. In tumor patients differentiation between primary or secondary cardiac neoplasm and thrombus is a frequent and knowingly difficult task to manage. To avoid complex and unnecessary surgical diagnostic procedures non-invasive methods are in favor. For initiation of adequate therapy and evaluation of prognosis, however, early and reliable diagnosis is mandatory. So far, echocardiography and magnetic resonance imaging represent the mainstay for cardiac imaging diagnosis. Recently, the new technique of CT-based tumor volume perfusion (VPCT) measurement has advanced to a potent, reliable, and easy to perform alternative for cardiac imaging. The purpose of this study was to review the existing spectrum of diagnostic modalities for characterization of cardiac masses in an oncologic patient cohort with emphasis on their strengths and limitations and to present the benefit from using the novel technique called VPCT for this purpose.